New species of Orasema (Hymenoptera: Eucharitidae) from Central and South America. Issue 9 (18th March 2020) - Heraty, John M.; Baker, Austin J.
ABSTRACT: Six new species of Orasema are described. Four species are placed into a newly recognised lasallei species group: Orasema lasallei sp. nov . (Costa Rica, Honduras, Mexico, Nicaragua), O. janzeni sp. nov . (Costa Rica), O. peckorum sp. nov . (Brazil) and O. vasquezi sp. nov . (Colombia). One species is placed in the wayqecha group, Orasema masneri sp. nov . (Ecuador). One other species is currently unplaced to species group, O. longinoi sp. nov . (Costa Rica). Orasema lasallei was taken from a nest of Pheidole vorax (Fabr.) and an undescribed species near O. longinoi from a nest of Pheidole dossena Wilson (Myrmicinae). The morphology of the digitate labrum is discussed with respect to other Eucharitidae.